Consider the left-hand side(LHS) [cot(x) + 1] / [cot(x) – 1]. We want to prove that this is equal to the right-hand side (RHS), that is, [1 + tan(x)] / [1 – tan(x)]. Thus, we have the following:
LHS = [cot(x) + 1] / [cot(x) + 1]
= { [cot(x) + 1] / [cot(x) – 1] }* { tan(x) / tan(x) }.
NOTE: We multiply tan(x) to cot(x) + 1 and the other tan(x) is multiplied to cot(x) – 1.
= { tan(x) [cot(x) + 1] } / { tan(x) [cot(x) – 1] }
= { tan(x) cot(x) + tan(x)] } / { tan(x) cot(x) – tan(x)] }, by distributive property of multiplication over addition (subtraction)
= { 1 + tan(x)] } / { 1 – tan(x)] }, since tan(x) cot(x) = 1 by reciprocal identity.
= RHS.
Indeed, [cot(x) + 1] / [cot(x) – 1] = [1 + tan(x)] / [1 – tan(x)]
2006-11-15 18:06:52
·
answer #1
·
answered by rei24 2
·
0⤊
0⤋
It is elementary as cot is in LHS and tan on RHS
convert cot to 1/tan
LHS = (cot x +1)/(cot x-1) = (1/tan x +1)/(1/tan x -1)
= ((1+tan x)/tan x)/((1-tan x)/tan x)
= (1+tan x)/(1-tan x) multiply numerator and denominator by tan x
2006-11-15 17:58:25
·
answer #2
·
answered by Mein Hoon Na 7
·
0⤊
0⤋
tan x/(a million-cot x) = tanx(a million+cot x) /(a million-cot^2 x) = (a million+tan x)/(a million-cot^2x) tan x/(a million-cot x) = tanx(a million-cot x) /(a million-cot^2 x) = (-a million+tan x)/(a million-cot^2x) upload the two to get 2 tan x/(a million-cot^2 x) = 2 tan^3x/(tan^2 x -a million) = - tan x tan 2x RHS = a million + sec x cosec x = a million + a million/cos x a million/sin x = (a million+ cos x sin x)/ cos x sin x
2016-12-30 13:09:21
·
answer #3
·
answered by ? 3
·
0⤊
0⤋
cot x+1/cot x-1 =? 1+tan x/ 1- tanx
(1 - tanx)(1 + cotx) =? (1 + tanx)(cotx - 1)
1 + cotx - tanx -1 =?cotx - 1 + 1 - tanx
cotx - tanx = cotx - tanx
2006-11-15 18:00:22
·
answer #4
·
answered by Helmut 7
·
0⤊
0⤋
U take LHS or RHS, get the other, just use cotx = 1/tanx or
tanx = 1/cotx,,, whichever side u are comfortable with,, just algebra (common denom) cracks...
2006-11-15 19:00:17
·
answer #5
·
answered by Sid Has 3
·
0⤊
0⤋
just divide (cotx+1)/(cotx-1) through by
cotx and you have (1+tanx)/(1-tanx)
it's that easy
i hope that this helps
2006-11-15 20:48:59
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋